1955
DOI: 10.1139/b55-004
|View full text |Cite
|
Sign up to set email alerts
|

STUDIES ON HEARTWOOD FORMATION AND STAINING IN SUGAR MAPLE, ACER SACCHARUM MARSH.

Abstract: Parenchyma cells of maple wood may live for more than a century though a considerable proportion die earlier. A few cells succumb each year making "heartwood" formation gradual. Post mortem deposits, primarily in the parenchyma cells, account for the deepened color of older maple wood. The pH, water content, and mineral content of the wood do not change appreciably with aging. Maple wood often becomes deeply stained. The stain is due to deposits in the parenchyma cells which, if killed before senescence sets i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
4

Year Published

1956
1956
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 0 publications
2
10
0
4
Order By: Relevance
“…The M class in both sugar maple and yellow birch contained more ash than the other two higher quality classes (S and R). This finding is in agreement with the results obtained by Good et al (1955), who also found that the amount of ash is higher in stained wood as compared to sound sugar maple sapwood. According to Shigo and Sharon (1970), the increase in mineral content is associated with the processes of discoloration and decay in the sugar maple.…”
Section: Chemical Compositionsupporting
confidence: 93%
See 1 more Smart Citation
“…The M class in both sugar maple and yellow birch contained more ash than the other two higher quality classes (S and R). This finding is in agreement with the results obtained by Good et al (1955), who also found that the amount of ash is higher in stained wood as compared to sound sugar maple sapwood. According to Shigo and Sharon (1970), the increase in mineral content is associated with the processes of discoloration and decay in the sugar maple.…”
Section: Chemical Compositionsupporting
confidence: 93%
“…This is mainly motivated by the low environmental impact and low carbon emissions resulting from the use of forest biomass as a source of energy. Also, it may not be achievable to meet the global increase in energy consumption without the contribution of biofuels (Hunt 2009;Demirbas 2010;Masia et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Thus ripewood was significantly more decomposed than functional sapwood, as previously observed in apple trees infected with T. versicolor (Kile and Wade, 1974) and in the pith of trees lacking true heartwood (Wikström and Unestam, 1976;Marks et al, 1986;Glass and McKenzie, 1989). Susceptibility of ripewood can be attributed to both the inactivity of parenchyma cells and loss of hydraulic integrity in the xylem, creating more favorable conditions for growth of most decay fungi (Good et al, 1955;Kile and Wade, 1975;Boddy and Rayner, 1983). Similarly, tree age affects the amount of discoloration and decay resulting in an enhanced susceptibility of ripewood to decay (Rishbeth, 1951;Good et al, 1955;Basham, 1958;Hart and Johnson, 1970;Kile and Wade, 1975;Wikström and Unestam, 1976;Lonsdale, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Wie bei Nafikernen anderer Laubbaumarten kommt es auch bei der Buche zu pH-Verschiebungen vom sauren in den neutralen Bereich. Hohe pH-Werte bleiben aber auf den Randbereich des Nafikerns beschrankt, ahnlich wie dies auch von GOOD et al (1955) in Farbkernholz von Acer saccharum beobachtet wurde. Auch das Vorkommen der bei Buche nachgewiesenen Fettsauren wurde haufig bei na£kernigem Holz anderer Baumarten festgestellt (BRILL et al 1981;WORALL und PARMETER 1982).…”
Section: Diskussionunclassified
“…Bei Naftkernen und bei ,,discolored wood" wurden haufig hohe Konzentrationen der alkaHsch wirkenden Kationen Kalium und Calcium festgestellt (GOOD et al 1955;SHIGO und SHARON 1970;MURDOCH 1981;WALTER 1991). Eine pH-Erhohung ware aus diesen Griinden auch ohne die Beteihgung von Mikroorganismen denkbar (KNUTSON 1968).…”
Section: Diskussionunclassified